Relationship between coronavirus disease 2019 and Parkinson’s disease - Musheyev, Yakubmiyer; Ftiha, Farage; Jradeh, Henry (International Journal of Research in Medical Sciences, 2021)
New literature shows that COVID-19 has negative effects on patients with Parkinson’s disease (PD). COVID-19 is known to produce neurological manifestations and infects the central nervous system. Similarly, the virus also causes neuromuscular complications and involves the peripheral nervous system. Studies show PD patients with a severe COVID-19 infection have a higher mortality rate, worsening in symptoms, and require an increase in drug dosage. These studies suggest that COVID-19 may lead to a more rapid onset of PD, or may increase the risk of developing PD. Furthermore, researchers observed that Motor and nonmotor symptoms significantly worsened in PD patients with COVID compared to PD patients.